2014
DOI: 10.1063/1.4895589
|View full text |Cite
|
Sign up to set email alerts
|

Constrained large-eddy simulation of laminar-turbulent transition in channel flow

Abstract: A constrained large-eddy simulation (CLES) of a laminar-turbulent transition in a temporally developing channel flow is performed. First, we confirm the capability of CLES to simulate this transition problem using the a priori Reynolds stress estimated from a direct numerical simulation. Based on the analysis of the Reynolds stress during the transition process, an intermittency factor is introduced in the Reynolds-averaged Navier–Stokes equation (RANS) model to account for the transition property. Two simple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 60 publications
1
23
0
Order By: Relevance
“…Our future work will be devoted to extending the CLES method to transitional problems. In fact, we have assessed the CLES method in a temporal transitional channel and demonstrated that the CLES has the ability to simulate transitional problems [17]. This work encourages us to apply the CLES in more complex transitional problems, for both incompressible and compressible flows.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Our future work will be devoted to extending the CLES method to transitional problems. In fact, we have assessed the CLES method in a temporal transitional channel and demonstrated that the CLES has the ability to simulate transitional problems [17]. This work encourages us to apply the CLES in more complex transitional problems, for both incompressible and compressible flows.…”
Section: Discussionmentioning
confidence: 96%
“…It was shown that the CLES method could successfully eliminate the LLM defect and correctly predict the skin-friction coefficient in the attached channel flow, and its capability to simulate the detached wall-bounded flow is comparable to that of the DES. Recently, Zhao et al [17] successfully applied the CLES to simulate the laminar-turbulent transition problem in a temporal evolving channel flow.…”
Section: Validations and Applications Of Cles Methods In Compressible mentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the computation domain is selected as a cubic box with a size of 2π /1.12δ × 2δ × 2π /2.1δ (δ is the channel half-width), which is the same as the ones used by Gilbert and Kleiser, [39] Schlatter et al, [31] and Zhao et al [37]. Periodic boundary conditions are used in the wall-parallel plane (i.e., the streamwise (x) and spanwise (z) directions), while the non-slip boundary conditions are assigned at walls (y = ±δ).…”
Section: Numerical Set-upmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19] In theoretical research, a boundary layer or a plane channel was usually selected as the canonical problem. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] In the present study, a K-type transition in a plane channel flow is chosen as the test case to assess the SISM model.…”
Section: Introductionmentioning
confidence: 99%